The fall of the house of usher and other writing - Poe, Edgar Allan (London : Penguin Books, 2003)
Presents a selection of critical writings, short fiction, and poetry by American author Edgar Allan Poe, including the title story in which a visitor to a gloomy mansion finds a childhood friend dying under the spell of a family curse.
Keywords: Fantasy literature, American; Books -- Reviews